Solvent-controlled racemic resolution of C3-symmetric trihydroxytribenzotriquinacenes - Wagner, Philippe; Rominger, Frank; Oeser, Thomas; Mastalerz, Michael (The journal of organic chemistry, 2020)
A racemic C-3-symmetric trihydroxytribenzotriquinacene was resolved on a large scale by fractional crystallization of the corresponding (1S)-camphanic esters, achieving both enantiopure enantiomers (>99% ee) in 35% and 32% yields. The method relies on a distinct solvent-controlled discrimination process between the diastereomers. The enantiopure trihydroxytribenzotriquinacenes were converted into four other enantiopure building blocks, which are valuable precursors for supramolecular and materials chemistry to illustrate the utility of the synthesized compounds.